(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Despite the transformative potential of advanced technologies such as Artificial Intelligence (AI) and soft robotics, the Indian apparel manufacturing sector exhibits a critical lag in achieving comprehensive, integrated digitalization. Implementation is hampered by systemic, multi-dimensional barriers. Analysis reveals these constraints include acute data fragmentation coupled with poor IT infrastructure; severe financial stress resulting from high implementation costs with an uncertain Return on Investment (ROI); and the persistent technical difficulty of automating the handling of limp, deformable fabrics. This report addresses this pervasive adoption gap by analyzing constraints across Technological, Organizational, and Environmental contexts. This research introduces the Apparel Technology Adoption and Supply Chain Resilience (ATASCR) framework to model the assimilation process necessary for industry modernization and strategic resilience. The empirical findings, based on correlation analysis, confirm that Market Demand (V3) is the dominant positive driver for adoption, while anticipated barriers like Limp Material Difficulty (V1) and Financial Strain (V2) show surprisingly weak or contrary correlation with the level of technology adoption (V4). Crucially, the analysis confirms that digital adoption (V4) is strongly associated with achieving Supply Chain Resilience (V5).